THE USE OF DIGITAL TECHNOLOGIES IN TEACHING RUSSIAN AS A SECOND LANGUAGE IN THE CONTEXT OF HOSPITAL PEDAGOGY - Zulfiya Abubakirovna Dekhambayeva; Gulnoz Ikramovna Akhmadaliyeva; Gulchiroy Otabekovna Kamolova (The Bioscan, 2026)
This article explores the effective use of digital technologies in teaching Russian as a second language within the framework of hospital pedagogy. For children undergoing medical treatment, remote and interactive learning formats not only maintain educational continuity but also help alleviate stress and anxiety associated with hospitalization.